2021
DOI: 10.1097/phm.0000000000001813
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Fluoroscopically Guided Genicular Nerve Radiofrequency Ablation for the Treatment of Chronic Knee Pain Due to Osteoarthritis

Abstract: The objective was to determine the effectiveness of fluoroscopically guided genicular nerve radiofrequency ablation for painful knee osteoarthritis. Primary outcome measure was improvement in pain after 6 mos. Secondary outcomes included the Oxford Knee Score and Western Ontario and McMaster Universities Osteoarthritis Index. Two reviewers independently assessed publications before October 10, 2020. The Cochrane Risk of Bias Tool and Grades of Recommendation, Assessment, Development, and Evaluation system were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In a double-blind, randomized controlled study by Choi et al [ 5 ], the 50% success rate with genicular RFA was 59% at three months. In a systematic review evaluating the efficacy of genicular RFA, at least 50% success rates at six months were reported to be between 49% and 74% [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a double-blind, randomized controlled study by Choi et al [ 5 ], the 50% success rate with genicular RFA was 59% at three months. In a systematic review evaluating the efficacy of genicular RFA, at least 50% success rates at six months were reported to be between 49% and 74% [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The group mean OKS and WOMAC scores improved in the individuals experiencing genicular RF compared with intra-articular steroid injection and hyaluronic acid injection. This study showed moderate-quality evidence that fluoroscopically guided genicular RF was effective for relieving pain associated with knee OA at a minimum of 6 months ( 56 ).…”
Section: Lower Limb Rf Treatmentsmentioning
confidence: 98%
“…Genicular nerve radiofrequency ablation (RFA) is a conservative pain management technique used to treat chronic knee pain. In a systematic review, Fogarty et al reported moderate-quality evidence for use of fluoroscopically guided genicular RFA for chronic knee pain 11 . Genicular RFA provided 49% to 74% of patients with ≥50% pain relief and was more likely to be successful than intra-articular corticosteroid injections or hyaluronic acid injections at the 6-month follow-up.…”
Section: Kneementioning
confidence: 99%